2024
DOI: 10.1097/hnp.0000000000000460
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Progressive Muscle Relaxation and Deep Breathing Exercise on Pain, Disability, and Sleep Among Patients With Chronic Tension-Type Headache

Abstract: A randomized control trial was conducted to assess the effectiveness of progressive muscle relaxation and deep breathing exercises on pain, disability, and sleep quality among patients with chronic tension-type headache. Of the 169 randomly selected patients, 84 performed the intervention and reported less pain severity and disability and better sleep quality after 12 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…An important implication of our findings is the need for adding or combining psychological interventions with the management of CTTH rather than pharmacotherapy alone since a possible bidirectional relationship between CTTH and psychological comorbidities could lead to more drug dependency in these patients. Nonpharmacological therapies such as progressive muscle relaxation and deep breathing exercise have shown effectiveness in regard to pain severity, frequency, and functional status among patients with CTTH [ 60 ]. Prospective studies are needed to confirm this bidirectional relationship.…”
Section: Discussionmentioning
confidence: 99%
“…An important implication of our findings is the need for adding or combining psychological interventions with the management of CTTH rather than pharmacotherapy alone since a possible bidirectional relationship between CTTH and psychological comorbidities could lead to more drug dependency in these patients. Nonpharmacological therapies such as progressive muscle relaxation and deep breathing exercise have shown effectiveness in regard to pain severity, frequency, and functional status among patients with CTTH [ 60 ]. Prospective studies are needed to confirm this bidirectional relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Videos were animation presentation of diaphragmatic breathing with quadriceps exercises in sitting, standing positions, and walking. Each video provided objective and description of diaphragmatic breathing with quadriceps exercises: slowly deep intake 5 seconds with straight leg raising, hold breath and knee stretching with ankle exion for 5 seconds then, slowly continuous blow the index nger as long as he/she could for 10,11,12,13,14,15,16,17,18,19, and 20 seconds, respectively (21 video presentations in each position).…”
Section: Withdrawal Of Participant Criteriamentioning
confidence: 99%
“…Effect of diaphragmatic breathing has important roles for health promotion in healthy individuals [6]. Deep and slow breathing reduced state anxiety in older adults, attenuate pain [8], increase lung capacity [9,10], improves digestion or gastroesophageal re ux [11], sleep [12], mood [13], and enhance better oxygenation [14]. Lung volume is resource of air ow for speaking and breathing is critical to speech.…”
Section: Introductionmentioning
confidence: 99%
“…On the third day after doing the breathing relaxation technique independently, the patient said he felt more relaxed and was able to control the pain he was experiencing. In several studies, breathing relaxation techniques have been shown to be effective in minimizing and controlling pain (Aritonang 2020;Gopichandran et al 2021). Deep breathing techniques can help patients with acute pain (Joseph et al 2022).…”
Section: Non-pharmacological Therapymentioning
confidence: 99%